Today’s Main Issues in the Field of Anti-Corruption - Tokhtamishovich, Ochilov (Indonesian Journal Publisher, 2024)
In the article, today all countries in the world are facing the problem of corruption. Freedom of life, which is the main condition for building a democratic society, requires transparency in all spheres of society, especially in economic and political activity, on the one hand, and on the other hand, social and legal control organized on a legal basis. That is why nowadays it is most urgent to improve the socio-legal control system in society, which fully protects human rights and ensures the transparent and open activity of all physical and legal entities, sometimes, especially in the field of national security, with a certain degree of restriction. remains one of the problems.